Distortion of sectoral roles in climate change threatens climate goals - Cohen-Shields, Naomi; Sun, Tianyi; Hamburg, Steven P.; Ocko, Ilissa B. (Frontiers in Climate, 2023)
The longstanding method for reporting greenhouse gas emissions – carbon dioxide equivalence (CO2e) – systematically underestimates methane-dominated economic sectors’ contributions to warming in the coming decades. This is because it only calculates the warming impact of a pulse of emissions over a 100-year period. For short-lived climate forcers that mostly influence the climate for a decade or two, like methane, this method masks their near-term potency. Assessing the impacts of future greenhouse gas emissions using a simple climate model reveals that midcentury warming contributions of sectors dominated by methane – agriculture, fossil fuel production and distribution, and waste – are two times higher than estimated using CO2e. The CO2e method underemphasizes the importance of reducing emissions from these sectors, and risks misaligning emissions targets with desired temperature outcomes. It is essential to supplement CO2e-derived insights with approaches that convey climate impacts of ongoing emissions over multiple timescales, and to never rely exclusively on CO2e.